2019
DOI: 10.1002/phar.2353
|View full text |Cite
|
Sign up to set email alerts
|

Use of Direct Oral Anticoagulants in Morbidly Obese Patients

Abstract: In 2016, the International Society on Thrombosis and Haemostasis (ISTH) published guidelines advising caution when using direct oral anticoagulants (DOACs) in patients with morbid obesity due to limited clinical efficacy and safety data supporting their use in this patient population. In this review, we analyzed published articles in the MEDLINE database (from inception through May 29, 2019), and the Cochrane Library, Google Scholar, and EMBASE databases (from inception through April 26, 2019) that evaluated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Rivaroxaban pharmacokinetic (PK) and pharmacodynamic (PD) studies indicate no significant impact of body weight on maximum concentration after the first dose (Cmax) or area under the curve (AUC) 46 . In contrast, apixaban Cmax, AUC, trough concentrations, half‐life and anti‐factor Xa activity were found to be reduced in obese patients compared to non‐obese, and dabigatran displayed reduced trough concentrations and Cmax 46‐48 . Edoxaban PK/PD data in obese patients are limited, but non‐renal clearance may increase with higher body weight 46,47 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rivaroxaban pharmacokinetic (PK) and pharmacodynamic (PD) studies indicate no significant impact of body weight on maximum concentration after the first dose (Cmax) or area under the curve (AUC) 46 . In contrast, apixaban Cmax, AUC, trough concentrations, half‐life and anti‐factor Xa activity were found to be reduced in obese patients compared to non‐obese, and dabigatran displayed reduced trough concentrations and Cmax 46‐48 . Edoxaban PK/PD data in obese patients are limited, but non‐renal clearance may increase with higher body weight 46,47 …”
Section: Resultsmentioning
confidence: 99%
“…48 Overall, retrospective cohorts of AF and VTE identified no significant differences between specific DOACs and warfarin for thromboembolism or major bleeding events. 48,49,51…”
Section: High Body Weightmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, a subanalysis of RE-LY data in regard to patients’ characteristics revealed that due to reduced drug exposure, decreased peak concentrations, and shorter half-lives, patients with obesity showed 21% lower estimated dabigatran plasma concentrations than patients with normal weight [25, 43, 44]. Another single-center, retrospective cohort study described a higher thromboembolic event rate among obese patients on dabigatran than among those on apixaban or rivaroxaban, suggesting an avoidance of dabigatran in obese patients until further studies would be conducted [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Given that routine monitoring of DOAC concentrations is difficult to interpret and may be subject to variability, DOACs are not recommended in obese patients defined as a body mass index (BMI) ≥40 kg/m 2 and weight ≥120 kg 93 . In‐depth considerations in morbidly obese patients and the data since the Scientific and Standardization Committee (SSC)/ISTH recommendation have been reviewed previously in this Journal 94 . Since this publication, there have been two additional meta‐analyses assessing the rate of stroke or systemic embolism (SSE) and major bleeding in NVAF patients with obesity and morbid obesity 92 …”
Section: Transplant‐specific Considerations For Doac Usementioning
confidence: 99%